Domestic market of confectional products in the aspect of general world development trends - Strashynska, Larysa; Nуkonenko, Andrii (My University, 2020)
The article analyzes the domestic market of confectionery products. It is emphasized that companies are experiencing strong internal competition that is associated with a decline in exports. The main groups of enterprises that produce confectionery are identified and their specificities are characterized. It is noted that in today's conditions confectioners compete for the customer in proven ways - reducing the cost and reducing the production of unprofitable products. It is emphasized that domestic production is the main source of market supply formation at present. Possibilities and ratings of leading market operators are presented. The dynamics of production and export of confectionery products during 2011-2018, as well as their production and export in the range of assortment groups are analyzed. It is emphasized that Ukrainian exporters do not fully exploit the potential of foreign trade with EU countries, since the European confectionery market is quite saturated and exporters are faced with the problem of access to Ukrainian products on the shelf of European trading networks. Further analysis of the trends of the confectionery market was carried out on the basis of consumer preferences research. It has been determined that the structure of demand for confectionery products is undergoing dramatic changes due to the trend of healthy eating. It is noted that the development of the global nutraceutical market is a steady trend, which generates new consumer benefits, which in turn contribute to the formation of a new culture of food consumption. So functional sweets have pretty good prospects. It is emphasized that in order to realize their opportunities to be successful, competitive in today's market, for rapid and flexible response to consumer changes, owners of confectionery brand need complex technological solutions. Therefore, manufacturers need to place clear emphasis on those moments of the technological process that will make the finished confectionery product to demanded end consumers, which in turn will increase their loyalty to the brand in the conditions of formation of a new culture of consumption of confectionery products. У статті проаналізовано вітчизняний ринок кондитерських виробів. Наголошено, що серед компаній спостерігається потужна внутрішня конкуренція, яка пов’язана із скороченням експорту. Визначено основні групи підприємств, які виробляють кондитерські вироби, та охарактеризовано їх специфіку. Зауважено, що в сучасних умовах кондитери змагаються за клієнта перевіреними шляхами – зниженням вартості і скороченням виробництва нерентабельної продукції. Наголошено, що головним джерелом формування пропозиції на ринку на теперішній час залишається вітчизняне виробництво. Подано можливості й рейтинги провідних операторів ринку. Проаналізовано динаміку виробництва й експорту кондитерських виробів протягом 2011-2018 рр., а також їх виробництво й експорт в розрізі асортиментних груп. Наголошено, що українські експортери не повною мірою використовують потенціал зовнішньої торгівлі з країнами ЄС, оскільки кондитерський ринок Європи є досить насиченим і експортери стикаються з проблемою доступу української продукції на полиці європейських торговельних мереж. Подальший аналіз напрямків розвитку кондитерського ринку було проведено на основі досліджень споживчих уподобань. Визначено, що у структурі попиту на кондитерські вироби відбуваються кардинальні зміни під дією тренду здорового харчування. Зазначено, що розвиток світового ринку нутріцевтиків становить стійкий тренд, що формує нові споживчі переваги, які в свою чергу, сприяють формуванню нової культури споживання харчових продуктів. Отже, у функціональних солодощів є досить гарні перспективи. Наголошено, що для реалізації своїх можливостей бути успішними, конкурентними на сучасному ринку, для швидкого і гнучкого реагування на споживчі зміни, власникам брендів кондитерського ринку необхідні комплексні технологічні рішення. Отже, виробникам необхідно розставити чіткі акценти на тих моментах технологічного процесу, які зроблять готовий кондитерський продукт затребуваним кінцевим споживачам, що в свою чергу посилить їх лояльність до бренду в умовах формування нової культури споживання кондитерської продукції.
Keywords: confectionery market; internal competition; consumer preferences; traditional markets; reformatting of the industry; customs tariffs; кафедра маркетингу; ринок кондитерських виробів; внутрішня конкуренція; споживчі уподобання; ринок збуту; переформатування галузі; тарифи митні; культура споживання; тренд здорового харчування; кафедра маркетингу